2015
DOI: 10.1007/s00106-015-0020-y
|View full text |Cite
|
Sign up to set email alerts
|

Höranstrengung bei Cochlea-Implantaten

Abstract: We conclude that bilateral CI use has some effect on reducing listening effort, but compared with unilateral use the effect is possibly not very great.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Audiometric measures consistently demonstrate improved sound localization and speech understanding in spatially separated noise among bilateral cochlear implant users (Laske et al 2009; Smulders et al 2016b; van Zon et al 2017). These findings are corroborated by patient-reported outcomes, which additional identify reduced listening effort, reduced burden of tinnitus, and security in redundancy as benefits of bilateral over unilateral cochlear implants (Olze et al 2012; Hughes & Galvin 2013; Arnoldner et al 2014; Schnabl et al 2015). These benefits are important to the HRQoL of individuals with hearing impairment and do not appear to be measured by available HSUV instruments (Dixon et al 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Audiometric measures consistently demonstrate improved sound localization and speech understanding in spatially separated noise among bilateral cochlear implant users (Laske et al 2009; Smulders et al 2016b; van Zon et al 2017). These findings are corroborated by patient-reported outcomes, which additional identify reduced listening effort, reduced burden of tinnitus, and security in redundancy as benefits of bilateral over unilateral cochlear implants (Olze et al 2012; Hughes & Galvin 2013; Arnoldner et al 2014; Schnabl et al 2015). These benefits are important to the HRQoL of individuals with hearing impairment and do not appear to be measured by available HSUV instruments (Dixon et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Traditionally, patients with bilateral hearing impairment are candidates for a single (unilateral) cochlear implant with the goals of restoring speech understanding and improving quality of life. Mounting evidence now supports bilateral implantation for reduced listening effort, and improved signal discrimination, sound quality, and localization (Culling et al 2012; Hughes & Galvin 2013; Schnabl et al 2015; Rana et al 2017). Bilateral cochlear implantation can be performed simultaneously, or sequentially with a second surgery for individuals who have already received a unilateral cochlear implant.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies suggest that the benefit of bimodal and bilateral hearing configurations over unilateral hearing might stem from having the ability to segregate and attend to a target sound stimuli. This can be related to better enjoyment and clarity of media (Kong et al, 2005;Dorman et al, 2008;Gfeller et al, 2008;Veekmans et al, 2009), lower listening effort (Noble et al, 2008;Dunn et al, 2010;Hughes and Galvin, 2013;Schnabl et al, 2015;Perreau et al, 2017;Sladen et al, 2018), and better quality of hearing (Summerfield et al, 2006;Noble et al, 2008;Kocak Erdem and Ciprut, 2019). The advantage of bilateral users over bimodal users might be caused by a mismatch between listening through a CI on one side and hearing aid on the other requiring compensations in working memory and attention to combine the streams of auditory information (Gifford and Dorman, 2019;Pieper et al, 2022).…”
Section: Relationships With Ssq Spatial Hearingmentioning
confidence: 99%
“…The advantage of bilateral users over bimodal users might be caused by a mismatch between listening through a CI on one side and hearing aid on the other requiring compensations in working memory and attention to combine the streams of auditory information (Gifford and Dorman, 2019;Pieper et al, 2022). Lower levels of listening effort and better quality of hearing suggests that a lower degree of cognitive resource recruitment is required for encoding stimuli perhaps due to its spatial hearing advantage (Noble et al, 2008;Schnabl et al, 2015;Hua et al, 2017) and lack of mismatched auditory information. This is corroborated by the results of this study in which CI users reporting better spatial hearing also showed greater working memory ability both in the visual and auditory modality (reading and listening spans).…”
Section: Relationships With Ssq Spatial Hearingmentioning
confidence: 99%
“…The present study contains unilateral, bimodal, and bilateral CI users who may have different subjective listening experiences, and thus different effort and demand requirements. For instance, bilateral CI users have reported a lower degree of listening effort compared to unilateral CI users (Hughes and Galvin, 2013;Schnabl et al, 2015;Kocak Erdem and Ciprut, 2019). The neural response of CI users may also have been limited by individual differences related to the user device, such as CI distortions to the speech envelope, and thus leading to no detectable changes in TRF amplitude at a group level that corresponded with listening effort and attention.…”
Section: General Effect Of Increasing Background Noise Levels On Trf ...mentioning
confidence: 99%